Evaluasi Pembelajaran Keterampilan Menulis Bahasa Jepang Pemelajar Pemula - Santiar, Lea (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2021)
The purpose of this study was to evaluate the process of learning writing Japanese for novice learner. Stakeholders expect to hire graduates with skillful Japanese competence. Nevertheless, teaching writing has a lot of constrains due to the time availability, checking and giving feedbacks to learners. The focus of this research is to identify the problems in conducting writing classes, in the terms of teaching materials, allocation of time, feedback and revision. Evaluation was conducted based on the study on process approach and product approach and the learning models of writing. The result shows that teaching writing at this level accommodates both the process approach and the result approach. Writing activity may exercise grammar, but at the same time writing may exercise critical thinking, on how to deliver facts and thoughts. Conclusions and suggestions from this research, namely learning writing composition may start at the novice stage. Coordination with other language skills is advisory, especially in sharing similar topic in order to frequently use same vocabulary and sentence pattern. Therefore, writing session may focus on paragraph writing and coherency of composition.